2017
DOI: 10.1080/02640414.2017.1349922
|View full text |Cite
|
Sign up to set email alerts
|

Knee extensor fatigue developed during high-intensity exercise limits lower-limb power production

Abstract: We investigated the association between changes in vastii electromyography (EMG) and knee extensor fatigue during high-intensity cycling, and the subsequent effect on lower-limb power and intermuscular coordination during all-out cycling. On two separate days, participants completed 30-s all-out cycling or 10-min of high-intensity cycling followed by 30-s all-out cycling. EMG for gluteus maximus (GMAX), rectus femoris (RF), vastii (VAS), hamstrings (HAM) and gastrocnemius (GAS); co-activation for GMAX/RF, VAS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Again, whether this is true following exercise at different intensities is not known. However, studies that have assessed either dynamic or isometric measures of fatigue have shown that these assessments are affected differently, according to the exercise intensity-duration relationship (Black et al, 2017;Hureau et al, 2014;Morris et al, 2012;O'Bryan et al, 2017;Thomas et al, 2016Thomas et al, , 2015. Thus, we expected changes in fatigue outcome of different amplitude after the different exercise intensities/durations.…”
Section: Introductionmentioning
confidence: 92%
“…Again, whether this is true following exercise at different intensities is not known. However, studies that have assessed either dynamic or isometric measures of fatigue have shown that these assessments are affected differently, according to the exercise intensity-duration relationship (Black et al, 2017;Hureau et al, 2014;Morris et al, 2012;O'Bryan et al, 2017;Thomas et al, 2016Thomas et al, , 2015. Thus, we expected changes in fatigue outcome of different amplitude after the different exercise intensities/durations.…”
Section: Introductionmentioning
confidence: 92%
“…For participation in this study, six males and four females (n = 10) accustomed to regular high-intensity exercise were recruited (age: 26 ± 4 years; height: 179 ± 6 cm; mass: 74 ± 11 kg; mean ± SD). Sample size calculations using G * Power software (version 3.0.10) determined a required sample size of n = 8 based on an alpha level of 0.05, a power level of 0.95, and the assumption that the fatiguing task would lead to large reductions in maximal force of the quadriceps during knee extension IMVC and maximal cycling power (effect size f > 0.6) (Babault et al, 2006;O'Bryan et al, 2017). Participants were free from any existing cardiovascular, musculoskeletal or neuromuscular disorders.…”
Section: Participants and Ethicsmentioning
confidence: 99%
“…The amplitude of these EMG signals was normalized to the peak EMG recorded during the maximal cycling effort performed at the end of the cycling warm-up during the same visit (Rouffet and Hautier, 2008;O'Bryan et al, 2014). An average EMG profile was calculated for VL and VM (VAS), while EMG profiles of the other muscles were considered separately (O'Bryan et al, 2014(O'Bryan et al, , 2017. Finally, we assessed variability in total force (F tot ) applied to the two pedals and EMG activity of the muscles across the participants by calculating variance ratios (VR) using the following equation:…”
Section: Maximal Cycling Trialsmentioning
confidence: 99%
See 1 more Smart Citation